2016
DOI: 10.1002/etc.3474
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of the SSD approach in scientific case studies for ecological risk assessment

Abstract: Species sensitivity distributions (SSDs) are used in ecological risk assessment for extrapolation of the results of toxicity tests with single species to a toxicity threshold considered protective of ecosystem structure and functioning. The attention to and importance of the SSD approach has increased in scientific and regulatory communities since the 1990s. Discussion and criticism have been triggered on the concept of the approach as well as its technical aspects (e.g., distribution type, number of toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 125 publications
(217 reference statements)
0
57
0
2
Order By: Relevance
“…Similarly, no significant differences in marine and freshwater HC5 values were observed in a comparison of 10 insecticides . Del Signore et al , in a critical review of SSDs and their uses for ecological risk assessment, concluded that there were no systematic or consistent differences in sensitivity between freshwater and marine taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no significant differences in marine and freshwater HC5 values were observed in a comparison of 10 insecticides . Del Signore et al , in a critical review of SSDs and their uses for ecological risk assessment, concluded that there were no systematic or consistent differences in sensitivity between freshwater and marine taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum number of species for deriving an SSD was eight, which was in accordance to the minimum sample size required for chemicals by the US Environmental Protection Agency and by the European Union (Del Signore et al. ). Data for SSDs were checked for normal distribution using the shapiro.test function in R (R Core team ).…”
Section: Methodsmentioning
confidence: 94%
“…Deriving species sensitivity distributions (SSDs) is a common method to quantify the risks of chemical stressors to biodiversity (Del Signore et al. ). These statistical distributions describe variation in species sensitivity related to a particular environmental factor (Posthuma et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSD method has been applied as a decision support tool in environmental protection and management since the 1980s, being formally adopted for the derivation of environmental guidelines in 1985 in the United States and 1989 in Europe (Stephan et al, 1985;van Straalen and Denneman, 1989). In the last 30 years, SSDs have been widely applied to develop risk thresholds and guidelines for eukaryotic communities to a variety of different local (e.g., nutrients and petroleum hydrocarbons) and global (e.g., temperature) stressors for compliance and spatial risk assessments (Del Signore et al, 2016).…”
Section: Novel Approaches To Assessing Microbial Community Responses mentioning
confidence: 99%